Sexual dimorphism in the neuro-endocrine regulation of bicycle ergometric test parameters in untrained individuals with dysfunction of the neuro-endocrine-immune complex - Ruzhylo, Sofiya; Fihura, Oksana; Zakalyak, Nataliya; Kovalchuk, Galyna; Żukow, Xawery; Popovych, Dariya (Journal of Education, Health and Sport, 2022)
Background. Ergometric physical working capacity (PWC) testing has a long tradition in occupational medicine. PWC can be tested, using performance indicators like VO2max or the mechanical power. However, the calculated by bicycle ergometry PWC in reality reflects the reaction of the autonomic nervous system to muscle load, which, in turn, is strong, but still not absolutely complete, correlates with VO2max as a real indicator of cardiorespiratory fitness. The purpose of this study is to clarify the relationship between PWC, calculated based on the result of two-stage bicycle ergometry, and the parameters of neuro-endocrine regulation as well as sexual differences in such relationships. Materials and Methods. The object of observation were 30 women 29-76 (49,4±11,0) years and 30 men 24-69 (47,4±12,0) years without a clinical diagnosis, but with the deviations from the norm in a number of parameters of the neuro-endocrine-immune complex as a manifestation of maladaptation. For estimation of PWC a two-stage bicycle ergometry used. Parameters of EEG, HRV and adaptation hormones levels registered twice with an interval of 4 or 7 days. Results. In men, PWC correlates negatively with plasma levels of cortisol (r=-0,52) and triiodothyronine (r=-0,47), but positively with levels of calcitonin (r=0,25) and testosterone (r=0,22). The coefficient of multiple correlation R=0,705. In women, the correlation of the twice lower PWC with cortisol and calcitonin is weaker (r=-0,31 and 0,18, respectively), and is absent with testosterone and triiodothyronine, instead it was found in relation to aldosterone (r=-0,24); R=0,394. The PWC regression model for men includes 6 HRV and 11 EEG parameters (R=0,846), while for women only the mode HRV (r=-0,56) and two EEG parameters (R=0,608). Conclusion. PWC levels in men are generally downregulated by cortisol, triiodothyronine, sympathetic tone, and θ-rhythm generating neurons, but upregulated by testosterone, calcitonin, vagal tone, and related α-rhythm generating neurons. In women, PWC levels are borderline downregulated by cortisol and aldosterone, but significantly upregulated by circulating catecholamines and β-rhythm generating neurons.